Model Pemasaran Digital sebagai Inovasi Pemasaran Produk Usaha Mikro Kecil dan Menengah - Susiyanto Susiyanto; Nunung Nurnilasari (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
Digital marketing is used to acquire customers, generate leads, promote brands, retain customers, increase the number of products sold, and ultimately increase profits economically. Digital marketing gives buyers access to all information about products and allows them to make buying and selling transactions online. In addition, as a seller, you will be able to monitor and satisfy your wants and needs without time or geographic boundaries. Digital marketing is able to make two-way communication to create awareness and community involvement for certain products and brands. This study aims to see how far marketing innovation is carried out by MSMEs (Micro, Small, and Medium Enterprises), especially with the use of digital technology. This research is a library research reviewing or discussing previous journals or research related to the topics discussed. The data analysis process was carried out by trivaluating data from journals, books, and other reference sources that were used as literature. The implementation of the digital marketing concept is a hope to develop the economic power of small, medium and small businesses. MSMEs can take advantage of digital technology, especially community networks for marketing their products. In addition to the low cost that does not require special skills, this marketing can reach consumers directly in an effective and efficient manner. The challenge is that sellers and buyers must keep abreast of digital technology developments to make buying and selling transactions easier. The advertisements submitted must also be attractive, thus sellers must be more innovative and creative in creating advertising content in digital media.